2021
DOI: 10.3390/app11177881
|View full text |Cite
|
Sign up to set email alerts
|

Simulation and Experimental Verification of the Thermal Behaviour of Self-Written Waveguides

Abstract: In this work, we investigated the optical response of a self-written waveguide (SWW) in detail by heating the structure from room temperature up to 60 °C. Previous results indicated a decrease in the optical transmission with increasing temperature for certain waveguide parameters. Based on new experimental measurements, we have identified material parameters resulting in opposite behaviour. An experimental setup was conceived to verify these results. Hereby, we were able to show that we can adjust material pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Based on the multiple beam paths in the setup it can be avoided that this signal change is due to a systematic drift of the laser intensity or other environmental effects. A previous theoretical study showed that this effect is based on different thermo-optical coefficients of core and cladding due to the higher light fluence which is achieved when writing the core compared to the external flood exposure step [16]. This again leads to an increasing refractive index difference at a temperature of 60°C compared to room temperature, resulting in an improved numerical aperture of the SWW.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the multiple beam paths in the setup it can be avoided that this signal change is due to a systematic drift of the laser intensity or other environmental effects. A previous theoretical study showed that this effect is based on different thermo-optical coefficients of core and cladding due to the higher light fluence which is achieved when writing the core compared to the external flood exposure step [16]. This again leads to an increasing refractive index difference at a temperature of 60°C compared to room temperature, resulting in an improved numerical aperture of the SWW.…”
Section: Resultsmentioning
confidence: 99%
“…We have demonstrated that an increasing temperature yields an increasing optical transmission of the SWW originating from different thermo-optical coefficients of the core and cladding after the writing and curing process, respectively. This results in a different change of the refractive index with an increasing temperature, finally obtaining a larger numerical aperture of the SWW [24,25].…”
Section: Resultsmentioning
confidence: 99%
“…Such interconnects can be integrated into a broad field of fabrication processes, such as photolithography [20,21], hot embossing [22] or direct laser ablation [23]. The unique properties of this interconnection also enables thermal sensing by monitoring the transmitted optical power [24,25]. It is also possible to connect multiple components directly with each other, which was realized so far only using structures with a single splitter combining multiple laser beams [12,26].…”
Section: Introductionmentioning
confidence: 99%
“…The investigation of optical components which replace or surpass the functionality of their electronic counterparts has become a very active field of research during the last decades 1,2 . Such elements are used for optical data transmission, customized illumination purposes, sensing or signal distribution [3][4][5][6][7] . Especially for the sensing part a wide variety of applications has been investigated, e.g.…”
Section: Introductionmentioning
confidence: 99%